“Signing off on the right side of History?” Relating in Louise Welsh’s apocalyptic trilogy - Marie-Odile PITTIN-HEDON (E-REA)
This article examines the way the Scottish writer Louise Welsh contributes to the trend of postapocalyptic fiction in the 21st century, with her plague times trilogy. Relying on the critical and theoretical writing of Michael Foessel, Jean-Paul Engélibert, Bertrand Gervais, Denis Mellier, Hélène Machinal and François Hartog, it shows that Welsh’s trilogy, which spans the whole catastrophe from the outbreak of the virus to the aftermath of the apocalypse, borrows from the essential tropes of the genre to reflect upon the necessity for humans to relate to their past and their future, but also to relate to themselves and to each other. Welsh depicts a presentist world, where the chaos of the pandemic has severed all connection to people’s past, which precludes any meaningful projection into the future. The temporal closure is given spatial treatment, and the characters in the last volume are turned into collectors of fragments from the material past and from the political past. Welsh also uses the generic codes of crime to recapture the severed link, or create a new one, and to question the new world order that her novels depict.